Fluorinated electrolytes for li-ion batteries: the lithium difluoro(oxalato)borate additive for stabilizing the solid electrolyte interphase - Xia, Lan; Lee, Saixi; Jiang, Yabei; Xia, Yonggao; Chen, George Z.; Liu, Zhaoping (American Chemical Society, 2017)
Fluorinated electrolytes based on fluoroethylene carbonate (FEC) have been considered as promising alternative electrolytes for high-voltage and high-energy capacity lithium-ion batteries (LIBs). However, the compatibility of the fluorinated electrolytes with graphite negative electrodes is unclear. In this paper, we have systematically investigated, for the first time, the stability of fluorinated electrolytes with graphite negative electrodes, and the result shows that unlike the ethylene carbonate (EC)-based electrolyte, the FEC-based electrolyte (EC was totally replaced by FEC) is incapable of forming a protective and effective solid electrolyte interphase (SEI) that protects the electrolyte from runaway reduction on the graphite surface. The reason is that the lowest unoccupied molecular orbital energy levels are also lowered by the introduction of fluorine into the solvent, and the FEC solvent has poorer resistance against reduction, leading to instability on the graphite negative electrode. To tackle this problem, two lithium salts of lithium bis(oxalato)borate and lithium difluoro(oxalato)borate (LiDFOB) have been investigated as negative-electrode film-forming additives. Incorporation of only 0.5 wt % LiDFOB to a FEC-based electrolyte [1.0 M LiPF6 in 3:7 (FEC−ethyl methyl carbonate)] results in excellent cycling performance of the graphite negative electrode. This improved property originates from the generation of a thinner and better quality SEI film with little LiF by the sacrificial reduction of the LiDFOB additive on the graphite negative electrode surface. On the other hand, this additive can stabilize the electrolyte by scavenging HF. Meanwhile, the incorporated LiDFOB additive has positive influence on the interphase layer on the positive electrode surface and significantly decreases the amount of HF formation, finally leading to improved cycling stability and rate capability of LiNi0.5Mn1.5O4 electrodes at a high cutoff voltage of 5 V. The data demonstrate that the LiDFOB additive not only exhibits a superior compatibility with graphite but also improves the electrochemical properties of high-voltage spinel LiNi0.5Mn1.5O4 positive electrodes considerably, confirming its potential as a prospective, multifunctional additive for 5 V fluorinated electrolytes in high-energy capacity lithium-ion batteries (LIBs).